Feminism in the borderscape: Juarense women against injustice - Mehan, Asma; Dominguez, Natalia (Frontiers in Sociology, 2024)
This article critically examines the feminist movement in Ciudad Juárez, Mexico, highlighting the struggles and activism of Juarense women against social injustices, particularly those exacerbated by machismo, the Narco War, and the manufacturing industry. The analysis explores the roots of machismo in Mexican culture, the impact of the maquiladora industry on women's lives, and the rise of feminist activism in response to these challenges. Emphasizing the intersection of gender violence and legal frameworks, the article incorporates feminist legal theory to argue for substantial legal reforms to combat the normalization of machismo and feminicide. It further discusses the resilience and determination of Juarense women, portraying their efforts as part of the broader global feminist movement.